Plauditus cestus (Provonsha & McCafferty, 1982) (Insecta: Ephemeroptera: Baetidae): New records from Virginia and the Northwest Territories, with notes on color variation - Melissa Gorski (Check List, 2014)
Plauditus cestus (Provonsha & McCafferty, 1982) is widespread in eastern and central North America. We provide new data from Virginia that fill a gap in the range of distribution and new data from the Northwest Territories that extend the range of the species by over 1900 km to the northwest. The Northwest Territories specimen represents a new larval color variant, with pronounced coloration of abdominal segment 6. We emphasize the need for additional sampling of aquatic habitats in the Far North.